THE INFLUENCE OF STRATEGIC INTANGIBLE RESOURCES ON SMALL AND MEDIUM ENTERPRISES (SMES) PERFORMANCE - Larabi Chouayb , Shaima Ahmad KH. Barakat , Tamma Elhachemi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this paper is to examine the moderating influence of organizational trust in the relationship between innovativeness, knowledge sharing and small and medium enterprises performance. Closed-ended question was used in this study, and the five-point Likert scale used for evaluation. 210 questionnaires distributed to owners/managers of small and medium enterprises (SMEs) operating in food and beverage industry. The primary data that have been collected are analyzed using descriptive and causal method, and using structural equation modeling 3.0 to analyze the existing relationship. The results show a positive and significant relationship between innovativeness and SMEs. In addition, the study shows a significant and positive relationship between knowledge sharing and SMEs, and organizational trust moderates the relationship between the antecedents and SMEs